Blocking of EphA2 on Endometrial Tumor Cells Reduces Susceptibility to Vδ1 Gamma-Delta T-Cell-Mediated Killing - Hudecek, Robert; Kohlova, Barbora; Siskova, Ingrid; Piskacek, Martin; Knight, Andrea (Frontiers in Immunology, 2021)
Background Endometriosis is a common gynecological disease characterized by the presence of endometrial tissue outside the uterus causing chronic inflammation, severe pain, and infertility. However, the innate immunity of gamma-delta (γδ) T lymphocytes in endometriosis has not been characterized. Women with endometriosis present numerous endocrine and immune dysfunctions and elevated risk for endometrial, ovarian, and breast cancers. The tyrosine kinase EphA2 is often overexpressed in cancer including endometrial carcinoma. Methods We analyzed Vδ1 and Vδ2 γδ T cells in peripheral blood and paired peritoneal fluid samples in endometriosis patients (n = 19) and compared the counts with that of age- and sex-matched healthy donors (n = 33) using flow cytometry. Vδ1 and Vδ2 T cells isolated from healthy donors were used against KLE, RL-95, and Ishikawa endometrial tumor cells in 4 h flow cytometric cytotoxicity assays. The EphA2 blocking studies were performed using antibody, small-molecule inhibitor ALW-II-41-27, and the CRISPR/Cas9. Results We determined Vδ1 T cells substantially reduced in patients’ peripheral blood (p < 0.01) and peritoneal fluid (p < 0.001). No differences were found for circulating Vδ2 T cells compared with peritoneal fluid samples. We observed inherent cytotoxic reactivity of Vδ1 and Vδ2 γδ T lymphocytes against endometrial tumor cells. Importantly, we found reduced specific lysis of EphA2-positive cell lines KLE and RL-95 by Vδ1 T cells in the EphA2 antibody blocking studies and by the EphA2 inhibitor. Furthermore, Vδ1 T-cell-mediated killing was significantly decreased in RL-95 cell EPHA2 knockout. Finally, potent cytolytic activity exerted by Vδ1 T cells was significantly reduced in EPHA2 knockouts in renal A-498 and colon HT-29 carcinoma cell lines. Conclusions We determined variable levels of Vδ1 and Vδ2 γδ T cells in endometriosis patients. We observed inherent cytotoxic reactivity of γδ T-cell subsets against endometrial cell lines. Specifically, we found that blocking of EphA2 expression resulted in significant inhibition of endometrial tumor killing mediated by Vδ1 γδ T cells. These results suggest that EphA2 is involved in tumor cell lysis and contributes to susceptibility to Vδ1 γδ T cells cytotoxic reactivity.